2013
DOI: 10.1080/19440049.2013.820846
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an LC-MS/MS method for the detection of phomopsin A in lupin and lupin-containing retail food samples from the Netherlands

Abstract: Phomopsins (PHO) are mycotoxins produced by the fungus Diaporthe toxica (also referred to as Phomopsis leptostromiformis). Lupin is the most important host crop for this fungus and PHO are suspected as cause of lupinosis, a deadly liver disease, in sheep. Lupin is currently in use to replace genetically modified soy in many food products available on the European market. However, a validated method for analysis of PHO is not available until now. In this work, a dilute-and-shoot LC-MS/MS-based method was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Such data sets are useful in aiming the assessment of dietary exposure to certain mycotoxin in the general population [225,226]. The major EU institution for such assessments is the European Food Safety Authority (EFSA), which formed the Comprehensive European Food Consumption Database, also called EFSA Comprehensive Database [227]. Global assessments are done by the Food and Agriculture Organisation (FAO) of the United Nations.…”
Section: Relevant Strategies For Data Collectionmentioning
confidence: 99%
“…Such data sets are useful in aiming the assessment of dietary exposure to certain mycotoxin in the general population [225,226]. The major EU institution for such assessments is the European Food Safety Authority (EFSA), which formed the Comprehensive European Food Consumption Database, also called EFSA Comprehensive Database [227]. Global assessments are done by the Food and Agriculture Organisation (FAO) of the United Nations.…”
Section: Relevant Strategies For Data Collectionmentioning
confidence: 99%
“…The authors observed that D3G was ineffective in evoking splenic cytokine or chemokine mRNA responses. Because D3G is poorly absorbed, the intestine can be a target for this toxin (De Nijs et al 2012;Nagl et al 2012Nagl et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several studies have been carried out to gather information about the occurrence of phomopsins and to improve analytical techniques. 10,11 It has been recently shown that D. toxica has the potential to grow and produce toxins on other legumes, e.g., peas and beans. 12 The main toxin, phomopsin A (PHO-A), is often accompanied by small amounts of phomopsin B (PHO-B).…”
mentioning
confidence: 99%